2011
DOI: 10.1523/jneurosci.1985-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Ions in the Pore of Glycine and GABA Channels Shape the Time Course and Voltage Dependence of Agonist Currents

Abstract: In the vertebrate CNS, fast synaptic inhibition is mediated by GABA and glycine receptors. We recently reported that the time course of these synaptic currents is slower when intracellular chloride is high. Here we extend these findings to measure the effects of both extracellular and intracellular chloride on the deactivation of glycine and GABA currents at both negative and positive holding potentials. Currents were elicited by fast agonist application to outside-out patches from HEK-293 cells expressing rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 56 publications
(84 reference statements)
1
43
0
Order By: Relevance
“…It has been recently demonstrated that intracellular chloride ions bind to specific sites in the GABA A R pore affecting the receptor gating2122. Our observations further extend the hypothesis that [Cl − ] i acts as a intracellular messenger exerting a feedback control on GABA A currents not only by interfering with GABA A R gating, but also by modulating the expression of GABA A R subunits.…”
Section: Discussionsupporting
confidence: 83%
“…It has been recently demonstrated that intracellular chloride ions bind to specific sites in the GABA A R pore affecting the receptor gating2122. Our observations further extend the hypothesis that [Cl − ] i acts as a intracellular messenger exerting a feedback control on GABA A currents not only by interfering with GABA A R gating, but also by modulating the expression of GABA A R subunits.…”
Section: Discussionsupporting
confidence: 83%
“…This phenomenon was absent in other patches. In wild-type receptors, the amplitude of this fast sag is correlated to the magnitude of the current (Pitt et al, 2008), suggesting it is an artifact related either to channel density effects on desensitization (Legendre et al, 2002) or to changes in chloride gradient (Moroni et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…time course and decay half time of desensitization underlie large cell-to-cell variability (20) due to many different parameters that may influence the kinetics, such as ligand concentration (16), the phosphorylation state of the intracellular TM3-TM4 loop (16,20), or the membrane potential (1,21,22). GlyR are basically selective for Cl Ϫ but also permeable to other anions and even to cations (23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%